Case Report: Assessment of primary myxofibrosarcoma in the left atrium using multimodal ultrasonography - Hu, Liyan; Wang, Zhaohui; Chen, Yu; Zhang, Xiaowei (Frontiers in Cardiovascular Medicine, 2024)
Primary myxofibrosarcoma of the heart, a rare cardiac malignancy, was diagnosed in a middle-aged female patient exhibiting progressive dyspnea following transthoracic echocardiography and pathological analysis. Postoperatively, the patient underwent chemotherapy and Lenvatinib mesylate therapy, with regular check-ups confirming her survival. After 10 months the patient is still alive and well.